2014
DOI: 10.1080/02772248.2014.952517
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity I: effect of profenofos and triazophos (organophosphates) and carbofuran and carbaryl (carbamates) toLabeo rohita

Abstract: 2014) Acute toxicity I: effect of profenofos and triazophos (organophosphates) and carbofuran and carbaryl (carbamates) to Labeo rohita, Toxicological & Environmental Chemistry, 96:3,[466][467][468][469][470][471][472][473] Profenofos and trizaophos (organophosphates) carbofuran and carbaryl (carbamates) are among the major toxicants polluting freshwater bodies, as well as exerting a significant effect on the health of fish. In this study, the 96 h LC 50 of the most commonly used organophosphates and carbamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to the data from JMPR database, the major metabolite of triazophos, 3-hydroxy-1phenyl-1,2,4-triazole, was of low acute oral toxicity in rats (LD 50 > 5000 mg/kg, bw) which was lower than triazophos (LD 50 = 26−82 mg/kg, bw), and the weight of the evidence from studies of genotoxicity suggested that this metabolite is of no genotoxic concern. 26 The LD 50 of methyl parathion in rats was 4−62 mg/kg, while the LD 50 of its main metabolite pnitrophenol was 616 mg/kg. The metabolites of 2-hydroxyimino-2-phenylacetonitrile, isopropyl salicylate, p-nitrophenol, and 3-hydroxy-1-phenyl-1,2,4-triazole were also harmful in the environment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data from JMPR database, the major metabolite of triazophos, 3-hydroxy-1phenyl-1,2,4-triazole, was of low acute oral toxicity in rats (LD 50 > 5000 mg/kg, bw) which was lower than triazophos (LD 50 = 26−82 mg/kg, bw), and the weight of the evidence from studies of genotoxicity suggested that this metabolite is of no genotoxic concern. 26 The LD 50 of methyl parathion in rats was 4−62 mg/kg, while the LD 50 of its main metabolite pnitrophenol was 616 mg/kg. The metabolites of 2-hydroxyimino-2-phenylacetonitrile, isopropyl salicylate, p-nitrophenol, and 3-hydroxy-1-phenyl-1,2,4-triazole were also harmful in the environment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The OP metabolites have a lower mammalian toxicity than their parent compounds. According to the data from JMPR database, the major metabolite of triazophos, 3-hydroxy-1-phenyl-1,2,4-triazole, was of low acute oral toxicity in rats (LD 50 > 5000 mg/kg, bw) which was lower than triazophos (LD 50 = 26–82 mg/kg, bw), and the weight of the evidence from studies of genotoxicity suggested that this metabolite is of no genotoxic concern . The LD 50 of methyl parathion in rats was 4–62 mg/kg, while the LD 50 of its main metabolite p -nitrophenol was 616 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Interruption in behavior of fish by pesticides makes the fish stressed and immunocompromised, making them susceptible to different kinds of pathogens and infections (Nwani et al, 2013). In freshwater fish Labeo rohita commonly known as Rohu , imidacloprid induced morphological and behavioral changes such as avoidance mechanisms, abrupt and sluggish swimming movement in all directions, occasional jumping and hitting on the walls of tank, rapid scale loss, mucous secretion, change in body color (Qadir and Iqbal, 2016), while organophosphates (profenofos, trizaophos) and carbamates (carbofuran, carbaryl) caused suffocation, lethargy, descending movement, irregular swimming, gulping before death (Mustafa et al, 2014) in the same fish. Also, fipronil resulted in shakings, twitching, dizziness, increased operculum movement, body curving, breathing troubles in Cyprinus carpio (common carp) (Ghaffar et al, 2018).…”
Section: Pesticide-induced Toxic Effects On Fishmentioning
confidence: 99%
“…exhibited by fish, suffocation, lethargy, fish rest at the bottom, irregular swimming, movement towards bottom, gulping before mortality (Mustafa et al, 2014). …”
mentioning
confidence: 99%